Gênero e maternidade política em literaturas africanas: um estudo sobre ventos do apocalipse e hibisco roxo - Oliveira, Ana Ximenes Gomes de (2020)
This thesis focuses on the study of gender and motherhood as political categories in front of the female subject belonging to two African societies, Nigeria and Mozambique, transposed in the novels Winds of the Apocalypse, by Paulina Chiziane, and Purple hibiscus, by Chimamanda N. Adichie. The corpus of this research presents narratives that inscribe the feminine as subjects tangenced by the patriarchal culture and subvert the imposed places of silence. Theorists such as Anne McClintock (2010), Bibi Bakare-Yusuf (2003) and Amina Mama (2013) were brought to the study, highlighting the need to understand gender as a category that permeates colonial and postcolonial experiences in Africa, as well as the need to locate unique experiences of women's struggle against discourse of subordination. Thus, non-fictional female orality emerges as a policy that also propagates knowledge, repositioning the female voice as a tool of transgression in culture and tradition, presenting the feminine as a subject of action and a modifying agent of places oppression. To build a deepening in the fictional universe of the authors on screen, we established a reflection on the production of female authorship in the mentioned African territories, pointing its connection from the enunciating female voice that erases masculinist values and practices, in the public and private environments, through literature. Thus, we observe motherhood through the political bias of analysis, as debated by Mary O'Brien (2007) and Andrea O'Reilly (2007) in feminist studies, acting as a place of strength and resistance among women, capable of generating changes in the following generations and questioning the historical narratives and their places of protagonization and power.